Democracy, Duplicity and Dimona: The United States of America, Israel and the Globe since 1949 - Hogan, Jacob Peter (University of Ottawa (Canada), 2010)
The thesis examines Western complicity in covertly aiding, concealing and covering up Israel's nuclear weapons program and the implications that process had on the Soviet Union and Egypt during the Cold War. At the circumvention of the democratic process, Dimona's history is defined by shadowy scientism, obsequious journalism, secretive bureaucracies, clandestine corporatism and great power imperialism. In late October 1956 Israel acquired from France an atomic weapons reactor, with construction beginning in the Negev desert at Dimona during late 1957 or early 1958. During the ensuing years Israel received heavy water from Norway and Great Britain and uranium from Gabon, Argentina and South Africa. The atomic project was covertly funded by private Jewish donations from Canada, London, Paris and Wall Street. As early as 1958 factions within the State Department, Atomic Energy Commission and CIA factions were cognizant of Dimona's existence yet the bureaucracy chose to remain silent. When Dimona was unveiled by the media in December 1960, the White House salaciously denied possessing any foreknowledge of the reactor's nature, status or origins. The CIA-controlled and Jewish-dominated U.S. media obsequiously followed the state script by informing the public that Dimona was dedicated towards peaceful ends. During the 1960s the U.S. conducted pre-arranged tours of the facility, provided Israel with uranium and missiles to guard the reactor, covered up Israel's nuclear ambitions following China's first atomic test in October 1964, and refused to pressure Israel to sign the 1968 Nuclear Non-Proliferation Treaty. Even though Dimona was the key catalyst of the conflict, the U.S. also suppressed Israel's nuclear program from emerging as the defining subject of the Six Day War. Armed with intelligence deriving from Israeli sources, in early 1966 the Kremlin began utilizing Cairo as a proxy mouth piece to rhetorically denounce Israel's atomic agenda as Soviet relations with Egypt and the Arabs grew more intimate. In a failed attempt to destroy the reactor, the U.S.S.R. instigated the Six Day War crisis by fabricating false intelligence concerning Israeli troop concentrations and overflying the reactor with its most advanced plane in late May 1967.
Keywords: History, Middle Eastern.; History, United States.